PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PRESEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN DI DISTRO MACH MERCH DI KOTA KENDAL - Dita Adityasto, 14.05.51.0247; Soliha, Euis (Students' Journal of Economic and Management, 2018)
The aim of this study is to examine brand image, product quality, and price perception on purchasing decision process at distro match merch Kota Kendal. Population of this research are all the consumer and buyer at distro mach merch Kota Kendal, Jawa Tengah. The method of taking data used in this study is from questionnaires for about 100 sample. Every question measured by likert scale with 5 answer rank, from strongly agree until strongly disagree. The data processed with SPSS22 program. Data analysis method used in this study is quantitatif analysis: validity test, multiple regression linear test, and test research model. The result is show that brand image, product quality, and price perception simultaneously and partially have a positive significamt influence on purchasing decision process. Keyword: Brand Image, Product Quality, Price Perception, Purchasing Decision Process